Protocol for generating an arbitrary quantum state of the magnetization in cavity magnonics - Sharma, Sanchar; Bittencourt, Victor A. S. V.; Kusminskiy, Silvia Viola (JPhys Materials, 2022)
We propose and numerically evaluate a protocol to generate an arbitrary quantum state of the magnetization in a magnet. The protocol involves repeatedly exciting a frequency-tunable superconducting transmon and transferring the excitations to the magnet via a microwave cavity. To avoid decay, the protocol must be much shorter than magnon lifetime. Speeding up the protocol by simply shortening the pulses leads to non-resonant leakage of excitations to higher levels of the transmon accompanied by higher decoherence. We discuss how to correct for such leakages by applying counter pulses to de-excite these higher levels. In our protocol, states with a maximum magnon occupation of up to ∼9 and average magnon number up to ∼4 can be generated with fidelity > 0.75.
Created from Fastlane, Scopus look-up
Keywords: cavity magnonics; quantum magnonics; yttrium iron garnet (YIG)